Migration of an Intrauterine Device (IUD) into the Bladder: A Case Report - Sani, Muhammad Mahbubi; Fadilla, Aulia Nur; Witanto, Annisa Nadhifa; Sakinah, Aulia; Virdayanti, Dian Puspita; Surahmad, Fakhri (Brawijaya Journal of Urology, 2025)
Introduction. Intrauterine device migration, a rare complication, refers to the movement of the intrauterine device to unintended locations, including the bladder. The following paper presents a case study illustrating intrauterine device migration into the bladder. Case. A 45-year-old woman, who has been using an intrauterine device for 15 months, was referred from the public health centre  because the intrauterine device thread was not found. She has been experiencing pain after urination for a week that hasn’t improved with medication. During a gynecological examination, no thread was found. An abdominal ultrasound examination revealed the intrauterine device was located in the bladder. Conclusion. The migration of an intrauterine device into the bladder is a rare complication that requires careful monitoring. Intrauterine device users with persistent urinary tract infection symptoms that do not improve should consider this possibility. Proper insertion procedures and regular placement assessments are essential.